History of Economy and Economy of History - Novikov, Gleb (Journal of Economic Sociology, 2017)
The XVIIIth April International Academic Conference on Economic and Social Development took place on 11–14 April 2017 at the National Research University Higher School of Economics (Moscow). A section on “Economic History” was organized in the conference and chaired by M. A. Davydov, professor of the School of Historical Sciences at the HSE. A wide range of topics was discussed, including economic nationalism in Europe, the saving behavior of peasants, soviet industrialization, and German emigration from Russia. Most presenters used of two approaches—either the historical study of economy or economic study of history. While the former tries to reveal how certain economic phenomena have resulted from the historical processes, the latter suggests looking more closely at various historical situations and exploring them in depth. Combinations of these two methods proves to be highly productive. The main speakers in this section were M. N. Baryshnikov (Herzen University, St. Petersburg), M. A. Davydov (HSE, Moscow), M. G. Fiveyskaya (RANEPA, Moscow), A. Magliulo (UNINT, Rome), A. V. Mamayev (Institute of Russian History of the Russian Academy of Sciences, Moscow), D. V. Maslov (MSRU, Moscow), N. Nenovski (Université de Picardie Jules Verne, Amiens), S. A. Salomatina (MSU, Moscow), D. E. Shestakov (Bank of Russia, Moscow). S. B. Ulianova (St. Petersburg Polytechnic University, St. Petersburg), T. Y. Valetov (MSU, Moscow), and A. Y. Volodin (MSU, Moscow).